Political Instability in Guinea-Bissau (Taylor & Francis, 2025)
How can we make sense of the persistent political instability in Guinea-Bissau, a small country that has hosted extensive international interventions and made world news headlines over several decades? This book tackles this question, arguing for the need to understand politics in Guinea-Bissau as intricately linked to and deeply embedded in transnational, regional and trans-regional dynamics. Taking a multidimensional approach, the book brings together international scholars who have studied politics in Guinea-Bissau and Africa for many years, at different levels and from diverse perspectives. Together, the contributors provide an up-to-date analysis of crucial actors and processes, whilst also putting them in historical perspective. The volume connects the study of politics in Guinea-Bissau to a range of empirical phenomena and theoretical debates that have wider relevance far beyond its borders. In this way, it enables a better understanding of regional and international politics, demonstrating how apparently marginal cases are not marginal at all, but are actively entangled in broader multi-dimensional politics. With important new perspectives and insights both on Guinea-Bissau, and wider regional dynamics, this book will be an important read for researchers and policy makers involved in African politics and security issues.